Supplementation of H1N1pdm09 split vaccine with heterologous tandem repeat M2e5x virus-like particles confers improved cross-protection in ferrets. Issue 4 (20th January 2016) - Music, Nedzad; Reber, Adrian J.; Kim, Min-Chul; York, Ian A.; Kang, Sang-Moo
Highlights: High immunogenicity of VLP containing five tandem repeats of M2 proteins in ferrets. M2e5x VLP with or without split vaccine improves cross protection in ferrets. Adjuvant-like effects of M2e5x VLP on split vaccine in ferrets. Ferrets with Split+M2 VLP show significantly improved cross-protection. Abstract: Current influenza vaccines induce strain-specific immunity to the highly variable hemagglutinin (HA) protein. It is therefore a high priority to develop vaccines that induce broadly cross-protective immunity to different strains of influenza. Since influenza A M2 proteins are highly conserved among different strains, five tandem repeats of the extracellular peptide of M2 in a membrane-anchored form on virus-like particles (VLPs) have been suggested to be a promising candidate for universal influenza vaccine. In this study, ferrets were intramuscularly immunized with 2009 H1N1 split HA vaccine ("Split") alone, influenza split vaccine supplemented with M2e5x VLP ("Split+M2e5x"), M2e5x VLP alone ("M2e5x"), or mock immunized. Vaccine efficacy was measured serologically and by protection against a serologically distinct viral challenge. Ferrets immunized with Split+M2e5x induced HA strain specific and conserved M2e immunity. Supplementation of M2e5x VLP to split vaccination significantly increased the immunogenicity of split vaccine compared to split alone. The Split+M2e5x ferret group showed evidence of cross-reactive protection, including faster recovery from weight loss, and reduced inflammation, as inferred from changes in peripheral leukocyte subsets, compared to mock-immunized animals. In addition, ferrets immunized with Split+M2e5x shed lower viral nasal-wash titers than the other groups. Ferrets immunized with M2e5x alone also show some protective effects, while those immunized with split vaccine alone induced no protective effects compared to mock-immunized ferrets. These studies suggest that supplementation of split vaccine with M2e5x-VLP may provide broader and improved cross-protection than split vaccine alone.